Literary Materials as a Foundation for English Language Education in Junior Secondary Schools - Iswahyudi, Sabrina Retnasari; Jabu, Baso; Salija, Kisman (Institut Agama Islam Negeri Palopo, 2024)
This study examines the efficacy of literature-based instruction in fostering English language proficiency among junior secondary school students in Makassar, Indonesia. Employing a mixed-methods research design, data were collected from 120 students and 8 teachers across four public junior high schools through classroom observations, semi-structured interviews, pre- and post-tests, and document analysis over one academic semester. Findings reveal that classes utilizing literary texts demonstrated significantly higher improvements in vocabulary acquisition (27.3%), reading comprehension (23.1%), and writing skills (19.7%) compared to control groups using conventional textbooks. Furthermore, qualitative analysis indicates enhanced student engagement, cultural awareness, and critical thinking skills when literature served as the primary instructional material. The study concludes that systematically integrated literary materials provide a comprehensive foundation for language development that addresses both linguistic competence and higher-order thinking skills essential for adolescent learners at this critical developmental stage.